SOME OBSERVATIONS ON MACROPORELLA RETICA ZANIN BURI 1965 DASYCLADACEAN GREEN ALGA FROM THE UPPER TRIASSIC (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The  biometric and morphological characters of Macroporella retica Zanin Buri 1965 from the type-locality (Aviatico - Lombardy) are described. On the basis of these observations, it has been possible to confirm that Macroporella retica represents a junior synonym of Griphoporella curvata,  as stated by Barattolo et al. (1993).
Keywords: Dasycladales; Taxonomy; Triassic (Rhaetian); Northern Italy.